MENINGKATKAN KARAKTER SELF LEADERSHIP MELALUI PENDEKATAN EXPERIENTIAL LEARNING PESERTA DIDIK KELAS X SMA NEGERI 76 JAKARTA - Sukarmo Sukarmo (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2019)
The purpose of this research is to increase the character of self leadership through experiential learning approach in students of X SMA Negeri 76 Jakarta. The subjects of the study were students of class X SMA Negeri 76 Jakarta who had the character of a low self leadership category that was taken as many as 30 learners. The research method used is research counseling action. The design and model of the research used are model Kemmis and Mc. Taggart consisting of 3 cycles. The research instruments used are self-leadership character tests, self assessment scales, and observation sheets. The results of the study obtained the data of the test results increased self-leadership between pretests and posttest which measures the level of understanding and application of the character self leadership students before the action is given acquired average score of 54.33 with a percentage of 67.92%, increased after action is administered through a classical tutoring service with experiential learning approach with an average obtained score of 64.10 with a percentage of 80.13%. The results of the self-leadership character questionnaire are known that aspects of self awareness, self-directed aspects, self-management aspects, and self-accomplishment aspects of learners experience A fairly positive improvement. The conclusion of this research is through a guidance service with experiential learning approaches can improve the character self-leadership of the students X grade SMA Negeri 76 Jakarta.